1999
DOI: 10.1046/j.1365-2893.1999.6120130.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of hepatitis C virus RNA predict non‐response to interferon therapy: comparison of two commercial assays

Abstract: We compared two commercial assays for quantification of serum hepatitis C virus (HCV) RNA to investigate whether pretreatment levels of serum HCV RNA could predict the outcome of interferon (IFN) therapy. The Amplicor HCV Monitor test is based on a single, combined reverse transcription and amplification reaction carried out by the Tth DNA polymerase using specific primers for the 5' untranslated (UTR) region. The Quantiplex HCV RNA 2.0 assay is based on specific hybridization of viral RNA by synthetic oligonu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Thus, the fact that the HCV MONITOR tests underestimate viral loads above 5.0 ϫ 10 5 IU/ml may not be a limitation. Indeed, several studies have shown that the first version of the AM-PLICOR HCV MONITOR test and the Quantiplex HCV test, which does quantitate viral loads above 10 6 copies/ml, are equally accurate for predicting response to therapy from baseline viral load (26,32). Future studies that use international units per milliliter as a standardized reporting format should identify a prognostic cut-off.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the fact that the HCV MONITOR tests underestimate viral loads above 5.0 ϫ 10 5 IU/ml may not be a limitation. Indeed, several studies have shown that the first version of the AM-PLICOR HCV MONITOR test and the Quantiplex HCV test, which does quantitate viral loads above 10 6 copies/ml, are equally accurate for predicting response to therapy from baseline viral load (26,32). Future studies that use international units per milliliter as a standardized reporting format should identify a prognostic cut-off.…”
Section: Discussionmentioning
confidence: 99%
“…The AMPLICOR products have been used successfully for diagnosis (10,12), prognosis (11,26,31,32), and monitoring therapy (13,35). Furthermore, a proficiency study found that laboratories using the first version of the qualitative AMPLI-COR HCV and quantitative AMPLICOR HCV MONITOR tests obtained more-accurate results than laboratories using either in-house reverse transcription (RT)-PCR HCV tests or other commercially available HCV tests (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleic acid amplification tests for HCV RNA have contributed to our understanding of the natural history of hepatitis C virus (HCV) infection and to the clinical management of chronic hepatitis C. Quantitative viral load tests are used for prognosis, [1][2][3][4][5][6][7][8][9] for evaluating new treat-ment regimens, 10 and for modifying treatment 11 or deciding whether to administer follow-up treatment. 12 A recent analysis of data from two multicenter studies indicates that pretreatment viral load, together with genotype, sex, age, and extent of fibrosis, can be used to decide whether patients should be treated with interferon plus ribavirin for 24 or 48 weeks.…”
Section: In Interferon-treated Patients the Patterns Of Viral Load Cmentioning
confidence: 99%